PENINGKATAN PENGETAHUAN ORANG TUA TENTANG PERAN VITAMIN D BAGI KESEHATAN ANAK DI MASA PANDEMI COVID-19 - Kartini Kartini; Patricia Budihartanti Liman; Kurniasari; Husnun Amalia (Universitas Trisakti, 2022)
It's been two years since the world faced the Covid-19 pandemic caused by Severe Acute Respiratory Syndrome-Corona Virus-2 (SARS-CoV-2) which is able to affect the human immune system. One strategy in overcoming this pandemic is to pay attention to the intake of nutrients that are suitable to support the activation of the immune system in fighting the virus. Since the pandemic, vitamin D has been widely consumed to boost the body's immunity. This compound is able to improve the function of physical barriers, modulate the immune response, both natural and adaptive, to fight infections, allergies, malignancies and autoimmune. Recently it has been widely revealed that vitamin D deficiency was associated with various diseases. The occurrence of vitamin D deficiency in children may be due to a lack of awareness about the importance of vitamin D for children's health and this condition is certainly related to parental knowledge. The purpose of this outreach was to increase parents' knowledge about the role of vitamin D for children's health, especially during the pandemic. This program carried out online at Primary school and Junior high school of Tarsisius 1, Central Jakarta. Parental knowledge about the role of vitamin D was assessed using a modified questionnaires from Hussein et al. 2018, before and after the outreach. Data collection using Google Form, data cleaning with Open Refine software and analysis with SPSS software version 23. The Mann-Whitney test obtained p<0,001 so it was concluded that knowledge of vitamin D between the two groups differed significantly